Traditional Iranian courtyards as microclimate modifiers by considering orientation, dimensions, and proportions - Farzaneh Soflaei; Mehdi Shokouhian; Seyed Majid Mofidi Shemirani (Frontiers of Architectural Research, 2016)
The effect of courtyards as microclimate modifiers on the sustainability of traditional houses in a region with BWks mesoclimate in Iran was explored. The principle behind traditional Iranian courtyards was investigated to identify the most influential physical–environmental characteristics that can effectively improve energy efficiency in contemporary residential buildings. A field study was performed to analyze various physical elements of six valuable traditional courtyard houses located in a region with BWks mesoclimate in Iran. These elements included the orientation, extension, rotation angle, dimensions, and proportions of enclosed and open spaces, as well as physical bodies (opaque walls), transparent surfaces (openings), and natural elements (water and soil). Results showed that most of the studied Iranian courtyards were particularly designed to enable orientation, dimension, and proportion to act as microclimate modifiers. All survey-based data were summarized and integrated to propose a physical–environmental design model for courtyards as a useful energy-efficient strategy for contemporary sustainable housing in a region with BWks mesoclimate. The proposed model can be generalized to all design cases located in areas with similar climatic conditions.